A comparative study and application of single shot noise models - Palmiano, Leon Badilla
Short noise models are relatively new class of streamflow models. These models were developed in an attempt to reproduce the asymmetrical behavior of daily streamflow data; typically a steep rise coupled with an exponential decay. The performance of these models, in rivers located on various areas classified under the Coronas climate classification, was evaluated by this study. Six slightly different models (three of which were called seasonal and the other three were referred to as harmonized models) were fitted to four rivers. Seasonality was introduced in the harmonized models, by taking the harmonic representations on the raw daily statistics. Then the test for the adequacy of the models as well as the degree of model fit was primarily measured in terms of the reproduction of the historical statistics. Results indicated that most of the models reproduced the lag-one serial correlation coefficients very closely while the mean and standard deviations were likewise adequately preserved. However, the reproduction of the skewness coefficient varied among the models. Moreover, the models showed appreciable differences in the simulation of the extreme values and total discharges.